Kepemimpinan Guru Wanita Dalam Pengelolaan Kelas - Sukirman Sukirman; Enung Hasanah (Jurnal Administrasi Pendidikan, 2021)
This study aims to determine the leadership of female teachers in managing classes in Muhammadiyah schools in the Pleret region, Bantul, Yogyakarta (DIY). This research uses a quantitative descriptive approach to classify the leadership abilities of female teachers in managing the class. The research was carried out in Muhammadiyah schools in the Pleret area, Bantul, DIY. Respondents in this study were 60 teachers who teach at Muhammadiyah schools in Pleret, Bantul. The data collection technique in this study was to use a questionnaire that was distributed to all research samples who were randomly selected. Based on the results of the research and discussion that has been carried out, it can be concluded that most of the female teachers in the Muhamamdiyah Pleret school, Bantul, have fairly good leadership abilities (83%) and 15% of female teachers have excellent leadership in managing learning. This is a natural potential possessed by Muhammmadiyah in Pleret Bantul, to continue to develop their abilities so that they become better in the future.